Keep calm and carry on: miRNA biogenesis under stress - Manavella, Pablo Andrés (2019)
MicroRNAs (miRNAs) are major post-transcriptional regulators of gene expression. Their biogenesis relies on the cleavage of longer precursors by a nuclear localized processing machinery. The evolutionary preference of plant miRNAs to silence transcription factors turned these small molecules into key actors during growth and adaptive responses. Furthermore, during their life cycle plants are subject to changes in the environmental conditions surrounding them. In order to face these changes, plants display unique adaptive capacities based on an enormous developmental plasticity, where miRNAs play central roles. Many individual miRNAs have been shown to modulate the plant response to different environmental cues and stresses. In the last few years, increasing evidence has shown that not only individual genes encoding miRNAs but also the miRNA pathway as a whole is subject to regulation in response to external stimulus. In this review, we discuss the current knowledge about the miRNA pathway. We dissect the pathway to analyze the events leading to the generation of these small RNAs and emphasize the regulation of core components of the miRNA biogenesis machinery.